eHealth literacy demands and cognitive processes underlying barriers in consumer health information seeking - Connie V. Chan; Jelena Mirkovic; Stephanie Furniss; David R. Kaufman (Knowledge Management & E-Learning: An International Journal)
Background: Consumer eHealth tools play an increasingly important role in engaging patients as participants in managing their health and seeking health information. However, there is a documented gap between the skill and knowledge demands of eHealth systems and user competencies to benefit from these tools. Objective: This research aims to reveal the knowledge- and skill-related barriers to effective use of eHealth tools. Methods: We used a micro-analytic framework for characterizing the different cognitive dimensions of eHealth literacy to classify task demands and barriers that 20 participants experienced while performing online information-seeking and decision-making tasks. Results: Participants ranged widely in their task performance across all 6 tasks as measured by task scores and types of barriers encountered. The highest performing participant experienced only 14 barriers whereas the lowest scoring one experienced 153. A more detailed analysis of two tasks revealed that the highest number of incorrect answers and experienced barriers were caused by tasks requiring: (a) Media literacy and Science literacy at high cognitive complexity levels and (b) a combination of Numeracy and Information literacy at different cognitive complexity levels. Conclusions: Applying this type of analysis enabled us to characterize task demands by literacy type and by cognitive complexity. Mapping barriers to literacy types provided insight into the interaction between users and eHealth tasks. Although the gap between eHealth tools, users’ skills, and knowledge can be difficult to bridge, an understanding of the cognitive complexity and literacy demands can serve to reduce the gap between designer and consumer.